Bakeng se Afrika: Digital Skeletal Repository: Advancing Biological Anthropology and Medical Research in South Africa - (:unkn) unknown (My University, 2024)
The Bakeng se Afrika (meaning “for Africa” in Sotho) digital skeletal repository is an Erasmus+ cofunded project amongst four national (South African) and four international institutions. The repository is based on twentieth-century skeletal material curated in three South African osteological collections: the Pretoria Bone Collection, the Human Osteological Research Collection, and the Kirsten Skeletal Collection. The skeletal material was scanned at the Micro-Focus X-ray Radiography and Tomography facility (MIXRAD) at the South African Nuclear Energy Cooperation, and X-Sight X-Ray Services, using a Nikon XTH 225 ST industrial computed tomography system (Nikon Metrology, Belgium). For each skeletal element, the best scanning parameters were selected according to the size and density of the bone. The original and reconstructed data is stored on a physical server at the University of Pretoria. The repository contains 3400 micro-XCT scans of both complete and partial skeletal elements, including crania, mandibles, maxillary dentition, humeri, radii, ulnae, hands, os coxae, femora, patellae, calcanei, vertebrae, and ribs. Researchers can enquire about accessing the data at the Forensic Anthropology Research Centre (forensicanthro@up.ac.za). Digital data can be applied across numerous disciplines, including biological and forensic anthropology, health sciences, and medicine.
Keywords: African Research